Examining differentiated instruction practices among secondary school Malay language teachers in Malaysia - Elmustian Elmustian; Zamri Mahamod; Edmund Austrus; Norhidayah Azni Mohamed Zohomi (Institute of Advanced Engineering and Science, 2026)
This research focuses on the teaching practices of secondary school Malay language teachers in the Klang District, specifically on implementing differentiated instruction (DI) approaches introduced by the Malaysian Ministry of Education in 2019. This study employed a quantitative research design using a descriptive survey approach. Preliminary findings show that many students lack interest in classroom learning (PdP) due to traditional teaching methods, contributing to difficulties in mastering the syllabus and poor performance in public examinations such as the Sijil Pelajaran Malaysia (SPM). A questionnaire-based survey of 146 teachers was conducted, with descriptive analysis revealing that the overall implementation of DI is moderate (mean=3.15, SD=0.427). Among the 10 assessed items, ‘implementing DI according to environmental conditions’ achieved the highest mean (3.29), while ‘implementing (daily lesson plans RPH) based on DI’ scored the lowest (2.95). The analysis showed no significant gender-based differences in implementation practices, and teaching experience was weakly negatively correlated with implementation effectiveness. These findings suggest the need for targeted professional development programs to enhance teachers’ readiness and competency in applying DI. The study underscores the importance of equipping teachers with the necessary skills to create inclusive and effective learning environments, which can improve student engagement and academic outcomes.